2021
DOI: 10.3390/plants10091969
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Lead Stress on Sage Plant by 5-Aminolevulinic Acid (ALA)

Abstract: Oxidative stress is imparted by a varying range of environmental factors involving heavy metal stress. Thus, the mechanisms of antioxidant resistance may advance a policy to improve metal tolerance. Lead as a toxic heavy metal negatively affects the metabolic activities and growth of medicinal and aromatic plants. This investigation aimed to assess the function of 5-aminolevulinic acid (ALA) in the alleviation of Pb stress in sage plants (Salvia officinalis L.) grown either hydroponically or in pots. Various c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…It also activates the antioxidant enzyme defence system, reduces lipid peroxidation, and protects plant organelles from damage ( Youssef and Awad, 2008 ; Xu et al., 2015 ). Further, El-Shora et al. (2021) also found that ALA reduced malondialdehyde (MDA) and ROS levels in S. miltiorrhiza and improved plant growth under lead stress.…”
Section: Introductionmentioning
confidence: 93%
“…It also activates the antioxidant enzyme defence system, reduces lipid peroxidation, and protects plant organelles from damage ( Youssef and Awad, 2008 ; Xu et al., 2015 ). Further, El-Shora et al. (2021) also found that ALA reduced malondialdehyde (MDA) and ROS levels in S. miltiorrhiza and improved plant growth under lead stress.…”
Section: Introductionmentioning
confidence: 93%